The average rate of change of the exponential equation from x = 3 to x = 6 is 4.55
How to determine the average rate of change?
The function is given as:
[tex]f(x) = 2x^{1.35[/tex]
When x = 3, we have:
[tex]f(3) = 2 * 3^{1.35} =8.813[/tex]
When x = 6, we have:
[tex]f(6) = 2 * 6^{1.35} =22.466[/tex]
The average rate of change is then calculated as:
[tex]m = \frac{f(6) -f(3)}{6 - 3}[/tex]
This gives
[tex]m = \frac{22.466 -8.813}{6 - 3}[/tex]
Evaluate
m = 4.55
Hence, the average rate of change of the exponential equation from x = 3 to x = 6 is 4.55
Read more about average rate of change at:
https://brainly.com/question/8728504
#SPJ1